2009
DOI: 10.1007/s11192-009-0122-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency measurement of research groups using Data Envelopment Analysis and Bayesian networks

Abstract: Applications of non-parametric frontier production methods such as Data Envelopment Analysis (DEA) have gained popularity and recognition in scientometrics. DEA seems to be a useful method to assess the efficiency of research units in different fields and disciplines. However, DEA results give only a synthetic measurement that does not expose the multiple relationships between scientific production variables by discipline. Although some papers mention the need for studies by discipline, they do not show how to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Due to research collaboration, scientific productivity, understood as efficient use of resources leading to high quality products, improves with variations across scientific fields (Abramo, D’Angelo, & Di Costa, 2009; Ruiz et al, 2010) and different patterns of internationalization as shown in cases from Europe (Abramo, D’Angelo, & Solazzi, 2011) and Latin America (Orozco & Villaveces, 2015). Besides the obvious condition of partners being from different nations, international research collaboration (IRC) produces impacts that are different to research collaboration between researchers from the same country.…”
Section: Introductionmentioning
confidence: 99%
“…Due to research collaboration, scientific productivity, understood as efficient use of resources leading to high quality products, improves with variations across scientific fields (Abramo, D’Angelo, & Di Costa, 2009; Ruiz et al, 2010) and different patterns of internationalization as shown in cases from Europe (Abramo, D’Angelo, & Solazzi, 2011) and Latin America (Orozco & Villaveces, 2015). Besides the obvious condition of partners being from different nations, international research collaboration (IRC) produces impacts that are different to research collaboration between researchers from the same country.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies include Bonaccorsi, Daraio and Simar (2006), where Italian universities are analysed, and Bonaccorsi and Daraio (2003), who consider institutes of the French INSERM and biomedical research institutes of the Italian CNR. Ruiz et al (2010) examine the efficiency in the scientific production of a sample of Colombian research groups. Agasisti, Catalano, Landoni and Varganti (2012) analyse the production of 69 academic departments located in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Vinkler (1998, 2006), Ruiz et al (2010), and Bonaccorsi et al (2006), for instance, developed composite (i.e., multidimensional) indicators for evaluating the research performances of research institutes.…”
mentioning
confidence: 99%
“… 1 Note that the use of multidimensional measures has not only been suggested for evaluating individual researcher performances, but also for evaluating research departments. Vinkler ( 1998 , 2006 ), Ruiz et al ( 2010 ), and Bonaccorsi et al ( 2006 ), for instance, developed composite (i.e., multidimensional) indicators for evaluating the research performances of research institutes. …”
mentioning
confidence: 99%
See 1 more Smart Citation